Immersion, social media and transmedia storytelling: the inclusive mode of reception - Gauthier, Philippe (Comunicación y Medios, 2018)
In the present text, I propose to initiate a discussion which will more directly interrogate the incorporation of social media into transmedia narratives through the creation of “official” accounts for fictional characters. My goal is to demonstrate through a case study of the transmedia story Marble Hornets (produced from June 2009 to June 2014) how the presence of fictional characters on social media creates new relations between their fictional world and the reality of the interactor – relations, moreover, which are accentuated by the use of mobile technologies. I will also discuss how these new relations force a reassessment of the concepts “immersion” and “the magic circle,” which were developed to better grasp the relations between fiction and reality created by more traditional media such as the novel, the graphic novel, television, cinema and video games.